Anatomy of molecular properties evaluated with explicitly correlated electronic wave functions. (17th October 2016) - Zhang, Jinmei; Calvin, Justus A.; Valeev, Edward F.
ABSTRACT: Static electric dipole and quadrupole moments were evaluated at the explicitly correlated second-order Møller–Plesset (MP2-F12) level for BH, CO, H2 O, and HF molecules. The electron correlation contributions to the multipole moments were further decomposed into the direct ( unrelaxed ) and indirect ( orbital response ) components; we found that both components are equally important for the conventional (MP2) contribution, whereas the F12 correction to these properties originates primarily from the orbital response effects. Finally, the direct contribution dominates in the perturbative Hartree–Fock basis set incompleteness (CABS singles) correction. Two basis set families were employed: the standard aug-cc-pVXZ series and the cc-pVXZ-F12 series designed specifically for the F12 methods. The aug-cc-pVXZ MP2-F12 multipole moments usually have smaller basis set errors than the cc-pVXZ-F12 counterparts, albeit their differences are small at the triple ( X = T ) and quadruple ( X = Q ) zeta level. With the MP2-F12 calculations, the basis set errors of dipole and quadrupole moments can be reduced to ∼0.001 a.u., or roughly 0.1%, at the aug-cc-pVDZ and aug-cc-pVTZ levels, respectively. Abstract :